2021
DOI: 10.21037/gs-21-443
|View full text |Cite
|
Sign up to set email alerts
|

Preparing PAMAM-NK4 nano complexes and examining their in vitro growth suppression effects in breast cancer

Abstract: Background: This study sought to examine the suppression of the NK4 (which is a fragment that originates from the trypsin digestion of the hepatocyte growth factor) gene as mediated by new nano material polyamidoamine (PAMAM) dendrimers in the growth of breast cancer cells MDA-MB-231 and MCF-7, and the therapeutic effects in a nude mice model of transplanted tumor cell MDA-MB-231. Methods: We built PAMAM-NK4 nano particles and detected the in vitro transfection rate. Nano complexes and blank plasmid PAMAM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The data indicated that such nanocomplexes were cytotoxic for U937 tumor cells via an apoptosis pathway and also provided fluorescence imaging of cancer cells. Similarly, M. Liu, Guo, et al (2021) described a new PAMAM‐NK4 nanocomplex and checked its efficiency in nude female mice with breast cancer. The PAMAM‐ NK4 nanocomplexes inhibited breast cancer in this model.…”
Section: Multifunctional Dendrimer‐based Nanoconjugates For Cancer Tr...mentioning
confidence: 99%
“…The data indicated that such nanocomplexes were cytotoxic for U937 tumor cells via an apoptosis pathway and also provided fluorescence imaging of cancer cells. Similarly, M. Liu, Guo, et al (2021) described a new PAMAM‐NK4 nanocomplex and checked its efficiency in nude female mice with breast cancer. The PAMAM‐ NK4 nanocomplexes inhibited breast cancer in this model.…”
Section: Multifunctional Dendrimer‐based Nanoconjugates For Cancer Tr...mentioning
confidence: 99%